ইলা মিত্র : নাচোলের তেভাগা আন্দোলনের নেত্রী - বেগম, মালেকা
On the life and works of Ila Mitra, born in 1925, a Bengali woman political activist and communist of East Pakistan, now Bangladesh; includes some letters, interviews and articles by and about her.